2022
DOI: 10.1111/vru.13207
|View full text |Cite
|
Sign up to set email alerts
|

Stifle joint osteoarthritis in small‐breed and medium‐breed dogs is more severe after cranial cruciate ligament injury than medial patellar luxation

Abstract: This retrospective observational study aimed to characterize the severity and distribution of OA in the stifle joints of small and medium dogs with CCL injury and/or MPL.Radiographs of the stifle joints from 218 dogs from 10 small and medium breeds were included; 127 joints had CCL injury, 76 joints had MPL, and 73 joints had CCL injury and MPL. OA was graded at 33 sites within the joint. The mean ± SD OA score was 20.3 ± 9.9. For all joints, OA was more severe in heavier than lighter dogs (P = 0.003).Joints w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…In dogs with CrCLD where menisci remain intact, even conservative treatment can have a functional outcome albeit including OA. In summary, it should be clear that canine CrCLD will lead to loss of joint function and progressive OA in all cases ( 93 , 94 ).…”
Section: Animals As Translational Research Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…In dogs with CrCLD where menisci remain intact, even conservative treatment can have a functional outcome albeit including OA. In summary, it should be clear that canine CrCLD will lead to loss of joint function and progressive OA in all cases ( 93 , 94 ).…”
Section: Animals As Translational Research Modelsmentioning
confidence: 99%
“…These techniques do have the potential decreasing internal rotation instability. Nevertheless, these artificial (93,94). Traumatic cruciate and collateral ligament lesions most commonly in combination with meniscal tears occasionally occur in dogs, but are more common in cats.…”
Section: Cranial Cruciate Ligament Diseasementioning
confidence: 99%
“…Previous studies have shown that breed predisposition plays a role in the development of OA. 2‐6 For example, boxers, Yorkshire terriers and West Highland white terriers typically present with higher OA scores than other breeds of similar sizes 3 , 4 …”
Section: Figurementioning
confidence: 99%
“…These conditions arise from bone inflammation and structural abnormalities [6]. If left untreated, prolonged MPL and CCLR can result in increased contact between the femur and tibia resulting in osteoarthritis [7].…”
Section: Introductionmentioning
confidence: 99%